GDP, Trade Tax, and Economic Distance's Influence on Ghana's Cocoa Trade with Trading Partners - Agbolosoo, John Atsu; Septya, Fanny; Novianti, Tanti (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2025)
Ghana prioritizes the production of raw cocoa beans while engaging in trade for other commodities. Although cocoa holds significant economic importance for Ghana, there is a notable gap in research regarding the economic factors influencing cocoa exports, especially between European and Asian markets. The effects of Gross Domestic Product (GDP), trade taxes, and economic distance on trade flows, market accessibility, and sustainability in these regions remain ambiguous. This study utilized panel data from 2001 to 2023, employing the gravity model through Panel Ordinary Least Squares (POLS), Generalized Least Squares (GLS), and Poisson Pseudo-Maximization Likelihood (PPML) estimation methods. The findings indicate that Ghana's bilateral cocoa trade with European and Asian markets is significantly influenced by Ghana's GDP, the economies of its trading partners, international trade taxes, and economic distance. To enhance Ghana's bilateral cocoa trade, forming trade agreements with emerging Asian economies could reduce barriers and improve market access. Ghana should consider revising cocoa export duties to increase competitiveness and negotiate with trade partners to lower import tariffs on its cocoa products in Asian markets.